2010
DOI: 10.1056/nejmoa1000931
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Treatment for Children with Peripartum Nevirapine Exposure

Abstract: BACKGROUND Single-dose nevirapine is the cornerstone of the regimen for prevention of mother-to-child transmission of human immunodeficiency virus (HIV) in resource-limited settings, but nevirapine frequently selects for resistant virus in mothers and children who become infected despite prophylaxis. The optimal antiretroviral treatment strategy for children who have had prior exposure to single-dose nevirapine is unknown. METHODS We conducted a randomized trial of initial therapy with zidovudine and lamivud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
216
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(227 citation statements)
references
References 20 publications
8
216
2
1
Order By: Relevance
“…Infected infants exposed to NVP during failed PMTCT (or in whom perinatal NVP exposure cannot be excluded) should be started on a boosted PI‐containing regimen, as transmitted resistance may lead to failure of NVP‐containing ART 64, 65. LPV/r should not be administered to premature neonates or to term neonates below 2 weeks of postnatal age because of the increased risk of toxicities reported in premature and very young babies 66, 67.…”
Section: Which Art Regimen To Start As First‐line Therapymentioning
confidence: 99%
“…Infected infants exposed to NVP during failed PMTCT (or in whom perinatal NVP exposure cannot be excluded) should be started on a boosted PI‐containing regimen, as transmitted resistance may lead to failure of NVP‐containing ART 64, 65. LPV/r should not be administered to premature neonates or to term neonates below 2 weeks of postnatal age because of the increased risk of toxicities reported in premature and very young babies 66, 67.…”
Section: Which Art Regimen To Start As First‐line Therapymentioning
confidence: 99%
“…By 12 months, the lopinavir/ritonavir (LPV/r)-based regimen was associated with fewer virologic treatment failures or deaths compared with the NVP-based regimen. However, improvements in CD4 percentage (CD4%) and growth (weight-for-age and height-for-age z score) marginally favored NVP [11,12]. To better understand the comparative long-term effect of these 2 ART regimens in an HIV-infected pediatric population, we present data from extended follow-up in this multicenter clinical trial.…”
mentioning
confidence: 99%
“…[18] In children started on ART >3 years of age, the PENPACT-1 study showed that, after 4 years on ART, viral suppression and CD4 + count were similar on NNRTI and PI-based ART. [19] Of note, the PI most commonly used was unboosted nelfinavir, an unacceptable choice given current knowledge.…”
Section: Rationale For the Current National First Regimenmentioning
confidence: 97%
“…[29] In the P1060 study, approximately 80% of children on LPV/r achieved a viral load of <400 copies/mL at week 24. [18] In the International epidemiologic Databases to Evaluate AIDS (IeDEA) cohort, children starting ART at around 3.5 years of age had a 20% rate of virological failure after 3 years. [30] The ARROW study confirmed this finding, with 83% of children on two NRTIs and an NNRTI having a viral load of <400 copies/mL after a median of 3.7 years on therapy.…”
Section: Outcomes In African Children On Artmentioning
confidence: 99%